STUDIES ON THE INFLUENCE OF ORGANIC FERTILIZERS ON THE GROWTH AND SOME BIOCHEMICAL PARAMETERS OF CHILLI (CAPSICUM ANNUM L. VAR) - S. P. ADHIKARY,; P. K. GANTAYET, (The Bioscan, 2012)
A pot culture experiment was conducted in botanical garden of Aska Science College campus to study the influence of different organic fertilizers on the growth parameters and bimolecular contents of Chilli plant. The results revealed that the vegetative growth viz: shoot length, root length, shoot weight and root weight of plants were increased 37.05%,49.69%,35.75% and 51.21% respectively in vermicompost treatment compared with control. Degree of influence was more in vermicompost treatment followed by cow dung compost and leaf compost. The similar trend of results were also noticed in chlorophyll, carbohydrate and protein content of 45 day’s old chilli plants. Vermicompost treatment plants were showed 43.58%, 41.26%, 42.46% increase of chlorophyll, carbohydrate and protein contents respectively over control. Among organic fertilizers, vermicompost showed significantly higher vegetative growth and bimolecular content. The pot experimental studies suggest the possibility of using vermicompost as source for crop improvement.